ВДОСКОНАЛЕННЯ БАГАТОРІВНЕВОГО ВИПРЯМЛЯЧА У СКЛАДІ ВОЛЬТОДОДАВЧОГО КАНАЛУ СИСТЕМИ ЖИВЛЕННЯ ПОСТІЙНОГО СТРУМУ ШЛЯХОМ ДЕКОМПОЗИЦІЇ ЙОГО ЕЛЕМЕНТІВ - Липківський, К.О.; Можаровський, А.Г. (Інститут електродинаміки НАН України, Київ, 2021)
In power systems with renewable energy sources, the output voltage level depends on a priori unstable meteorological environmental conditions. This requires the introduction of an energy storage device (storage battery) into such systems and the organization of an appropriate booster channel (BC). In the output stage of the BDK, various types of transformer-and-switches executive structure (TSES) are used, in particular, multilevel rectifiers (MLR), one of the quality indicators of which is the efficiency of using semiconductor devices. In order to increase this indicator, it is proposed to perform the decomposition of the MLU from two series-connected blocks, which made it possible to synthesize new circuitry solutions for the TSES of this type. The possibility of achieving the desired accuracy of maintaining the output voltage with a limited number of semiconductor devices has been confirmed on specific examples. References 14, tables 2, figures 4.